Numerical study on the cyclic response of AFRP reinforced columns with externally unbonded energy dissipaters. Issue 2 (1st February 2018) - Efe, Steve; Shokouhian, Mehdi; Head, Monique; Chinaka, Emmanuel
Abstract: Fiber-reinforced polymer bars are gaining increased use in the construction market as a replacement to steel reinforcement for concrete structures. However their use as compression members is limited due to their mechanical properties, typically low flexural rigidity, so that local buckling may occur relatively at low stress levels. Their premature rupture in reinforced concrete (RC) columns could be eliminated by enhancing the columns' response elastically and concentrating damage to the externally installed, replaceable post-tensioned structural fuses. This paper is part of a larger numerical and experimental investigation to develop and validate design methods for a rocking aramid fiber reinforced polymer (AFRP) reinforced concrete column. The numerical study, implemented using the Extreme Loading for Structures software, consists of a total of thirteen columns. The columns were subjected to axial load followed by cyclic lateral load up to failure to examine the effectiveness of the rocking connection and overall response. The effect of key variables such as longitudinal bar ratio, structural fuse sizes and tie spacing was investigated. Ductility and energy dissipation gains of the rocking AFRP RC columns were compared to that of the conventionally reinforced steel column, and expected performance of the rocking connection was achieved.